Urban development practice versus the politics of memory in Irkutsk - Gimelshteyn, Alexander; Gimelshteyn, Irina (project baikal, 2026)
Large volumes of housing construction in Irkutsk create opportunities for expanding the godonymic space, that is, the totality of names of linear geographical objects officially fixed on the territory of the city, exercising the powers to name streets, alleys, squares, territories. However, in practice, developers with the tacit consent of local authority are sabotaging this.
Keywords: toponymic landscape; housing construction; identity; marketing